Recent Advances in Photoinduced Oxidative Cleavage of Alkenes - Hussain, Waseem A.; Parasram, Marvin (Synthesis, 2023)
Oxidative cleavage of alkenes leading to valuable carbonyl derivatives is a fundamental transformation in synthetic chemistry. In particular, ozonolysis is the mainstream method for the oxidative cleavage of alkenes that has been widely implemented in the synthesis of natural products and pharmaceutically relevant compounds. However, due to the toxicity and explosive nature of ozone, alternative approaches employing transition metals and enzymes in the presence of oxygen and/or strong oxidants have been developed. These protocols are often conducted under harsh reaction conditions that limit the substrate scope. Photochemical approaches can provide milder and more practical alternatives for this synthetically useful transformation. In this review, we outline recent visible-light-promoted oxidative cleavage reactions that involve photocatalytic activation of oxygen via electron transfer and energy transfer. Also, an emerging field featuring visible-light-promoted oxidative cleavage under anaerobic conditions is discussed. The methods highlighted in this review represent a transformative step toward more sustainable and efficient strategies for the oxidative cleavage of alkenes.1 Introduction2 Photochemical Methods for Oxidative Cleavage of Alkenes under Aerobic Conditions2.1 Transition-Metal-Catalyzed Oxidative Cleavage of Alkenes under Visible Light2.2 Photopromoted Organocatalyzed Oxidative Cleavage of Alkenes2.3 Oxidative Cleavage of Alkenes with Molecular Iodine under Visible Light2.4 Polymer-Catalyzed Oxidative Cleavage under Visible Light Irradiation2.5 Oxidative Cleavage via Direct Visible Light Excitation with Molecular Oxygen3 Anaerobic Oxidative Cleavage of Alkenes under Visible Light4 Conclusion
Keywords: oxidative cleavage; alkenes; ozonolysis; nitroarenes; photochemistry; anaerobic; visible light; aerobic